2012
DOI: 10.1007/s00125-012-2728-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a common variant of the PCSK2 gene on reduced insulin secretion

Abstract: Aim/hypothesis Individuals at risk of developing type 2 diabetes show a progressive decline in insulin secretion and increased insulin resistance over time. However, inability of the beta cells to compensate for the increased insulin resistance represents a key defect leading to overt type 2 diabetes. The aims of the present study were to replicate the association between genetic variants of the PCSK2 gene and insulin secretion, and to explore the effect on risk of type 2 diabetes. Methods Replication of PCSK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…A significant difference in the allele frequency distribution of a simple CA tandem-repeat DNA polymorphism (STRP) in intron 2 of PCSK2 has been reported in a case-control study of T2DM patients and normal controls in a Japanese population 26 ( Table 5 ). Jonssan et al recently reported that the C allele of PCSK2 rs2208203 in intron 2 was associated with reduced insulin secretion measured as the corrected insulin response as well as disposition index 40 . The variant was also associated with lower fasting glucagon levels in non-diabetic individuals with FPG over 5.5 mmol/l 40 ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in the allele frequency distribution of a simple CA tandem-repeat DNA polymorphism (STRP) in intron 2 of PCSK2 has been reported in a case-control study of T2DM patients and normal controls in a Japanese population 26 ( Table 5 ). Jonssan et al recently reported that the C allele of PCSK2 rs2208203 in intron 2 was associated with reduced insulin secretion measured as the corrected insulin response as well as disposition index 40 . The variant was also associated with lower fasting glucagon levels in non-diabetic individuals with FPG over 5.5 mmol/l 40 ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the expression of genes related to metabolic and immune functions. Ins1 was decreased in 8-day BBdp rats, while expression of Pcsk2, a proprotein convertase that participates in both insulin and glucagon production, was upregulated (Jonsson et al 2012) (Fig. 4A); Pcsk1 was unchanged.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Therefore, they may regulate growth hormone and downstream hormone production, including IGF1 and possibly also insulin. Pcsk2 was reported to be involved in processing insulin, glucagon, somatostatin, and amylin (43)(44)(45). Here, we show for the first time that IGF1 is significantly reduced when Pcsk2 is depleted.…”
Section: Continuous and Time-specific Genetic Regulation Of Igf1 In Dmentioning
confidence: 49%